1970
DOI: 10.1002/aic.690160416
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface active agents on liquid‐liquid mass transfer rates

Abstract: An interferometric investigation of the transfer of n-and iso-butyl alcohols from water to carbon tetrachloride revealed the existence of large interfacial resistances (500 to 2,500 sec./cm.) attributable to the presence of surface active agents. Evidence of a solute-surfactant interaction has been obtained with sodium dodecyl sulfate and sodium tetradecyl sulfate, but the effect appears to be much less pronounced with the shorter chain length surfactant or with the branched chain alcohol.The influence which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Insoluble surfactant monolayers forming solid-type surfactant films have also been reported to produce interfacial diffusional barriers for various solutes in aqueous solution (Burnett and Himmelblau, 1970;Plevan and Quinn, 1966). Soluble surfactants forming Gibbs monolayers generally do not exhibit barrier effects, a t least for small diffusing species, although there is some disagreement on this point (Plevan and Quinn, 1966;Springer and Pigford, 1970;Mudge and Heideger, 1970).…”
Section: Eflects Of Surfactants On Mass Transfermentioning
confidence: 95%
“…Insoluble surfactant monolayers forming solid-type surfactant films have also been reported to produce interfacial diffusional barriers for various solutes in aqueous solution (Burnett and Himmelblau, 1970;Plevan and Quinn, 1966). Soluble surfactants forming Gibbs monolayers generally do not exhibit barrier effects, a t least for small diffusing species, although there is some disagreement on this point (Plevan and Quinn, 1966;Springer and Pigford, 1970;Mudge and Heideger, 1970).…”
Section: Eflects Of Surfactants On Mass Transfermentioning
confidence: 95%
“…The results of Blokker [13], Davies and Wiggill [14], Mudge and Heideger [15], indicated decreased mass transfer in the presence of surfactants in ternary systems. This effect was attributed either to a mechanical resistance (barrier effect) or the dampening of Marangoni convection at the interface caused by the formation of a rigid interfacial film.…”
Section: Mass Transfer Coefficient and Extraction Efficiencymentioning
confidence: 99%
“…On the molecular level, the presence of surfactant molecules at a gas-liquid interface affects the mass transfer rate of a solute from the liquid to the gas by altering the interfacial region and providing additional resistance to diffusion through formation of a "condensed" layer of adsorbed surfactant [55,56]. Numerous studies have shown that the presence of adsorbed surfactant film at the interfaces retards the diffusion across interface in gas-liquid [57][58][59][60] and liquid-liquid systems [61][62][63]. Quantifying the individual mass transfer coefficients (i.e., k l , k m , and k g ) is beyond the scope of this study.…”
Section: Hollow Fiber Membrane Air-stripping Resultsmentioning
confidence: 99%